Strengths and weaknesses of the competitiveness of the Bulgarian economy - Marikina, Maria (Leadership, Society, Strategic Visions, 2021)
Competitiveness is an actual and important issue of economic theory and practice. It is a challenge to highlight the current understanding of her, to present and analyze the spectrum of factors underlying her, and to reveal opportunities for implementing policies to manage. The report presents a survey at the macroeconomic level, and the object of the surveys is the competitiveness of the Bulgarian economy. The scientifi c community has an interest in such an understanding, but it would be a good study to explore the strengths and weaknesses of the competitiveness that is the subject of the study. The aim is to make them systematized and serve as a reference for the most appropriate policy. In order to achieve this, the following tasks are envisaged: 1) Identifying and analyzing the essence and basic concepts of the competitiveness ategory at macro level. 2) Analyzing the current competitiveness in Bulgaria. 3) Assessment of the strengths and weaknesses of the competitiveness of the Bulgarian economy.4) To formulate conclusions and recommendations for our national competitiveness and possible policy decisions.